STUDI NUMERIK KARAKTERISTIK DISTRIBUSI ALIRAN DAN TEMPERATUR PADA PENDINGIN OLI PELUMAS DENGAN VARIASI MULTI-STEP BLOCKER - Duratun Nasiqiati Rosady, Siti; Novita Sari, Eli; Maknunah, Jauharotul (Politeknik Negeri Banyuwangi, 2022)
Lube oil cooler serves to lower the temperature of the lub eoil in the gas turbine lubrication system. The problem that often occurs is the oil exit temperature is still high. This causes process failure in the lubrication system because the working temperature exceeds the allowable temperature. This failure is caused by non-uniformity flow distribution of the lube oil cooler. Therefore, further studies are needed to improve the uniformity of flow distribution. To increase the uniformity of flow, modification of the shape of the inlet header and variations of the lubricating oil capacity on the performance of the lubricating oil cooler were carried out. The research method used is numerical simulation with ANSYS FLUENT software. The simulation is carried out in 3 dimensions with a turbulence model in the form of k-ε RNG using a pressure based solution solver. Making geometry and design specifications using GAMBIT software. Geometric data is the dimensions of the lubricating oil cooling system and data from previous studies. The simulation is carried out in the form of a base line header with a modification of the inlet header, namely a multi-step blocker with variations of the Reynolds Number of 3088, 5146, and 7616. Based on the results of numerical simulations that have been carried out, the lowest Non-uniformity flow rate is at Re = 3088 sebesar, Ф = 0.01594, Exit Temperature 76.620 oC, and Pressure Drop 639.265 N/m2.